1213 Cycling-related Trauma Admissions to the Major Trauma Centre in the Cycling Capital of the United Kingdom. (12th October 2021) - Arshad, Z; majeed, M; Thahir, A; Anwar, F; Rawal, J; Hull, P; Carrothers, A; Chou, D
Abstract: Aim: The number of cyclists travelling on roads in the United Kingdom (UK) is increasing. The government has recently introduced initiatives to promote cycling uptake and so these numbers are likely to increase. This study aims to characterise cycling related injuries presenting to a major trauma centre located within a region with the highest rates of cycling in the UK. Method: A retrospective review of cycling related trauma admissions occurring between January 2012 and June 2020 was performed. All patients were split into three groups based on the mechanism of injury. Our institution's electronic patient record system was used to collect data including age, gender, mechanism of injury, Glasgow coma scale score on arrival, incident date and time, injured body regions, 30-day mortality, helmet use, and length of stay. Results: A total of 606 cycling related trauma cases were identified, with 52 being excluded due to incomplete data. The 'cyclist v vehicle' group was associated with a significantly higher Injury Severity score (ISS), lower GCS and longer hospital stay than the other two groups. Helmet wearers were significantly older than non-wearers and helmet use was associated with a significantly reduced risk of head injury, lower ISS and higher GCS. Conclusions: With a likely increase in future cycling uptake, it is crucial that effective interventions are put in place to improve the safety of cyclists. A multi-faceted strategy involving driver and cyclist education, road infrastructure changes and helmet promotion campaigns targeting the younger generation could be employed.